A review of nanofluid heat transfer and critical heat flux enhancement—Research gap to engineering application - Wu, J.M. (2013)
As a novel strategy to improve heat transfer characteristics of fluids by the addition of solid particles with diameters below 100 nm, nanofluids exhibit unprecedented heat transfer properties and are being considered as potential working fluids to be used in high heat flux systems such as electronic cooling systems, solar collectors, heat pipes, and nuclear reactors. The present paper reviews the state-of-the-art nanofluid studies on such topics as thermo-physical properties, convective heat transfer performance, boiling heat transfer performance, and critical heat flux (CHF) enhancement. It is indicated that the current experimental data of nanofluids thermal properties are neither sufficient nor reliable for engineering applications. Some inconsistent or contradictory results related to thermo-physical properties, convective heat transfer performance, boiling heat transfer performance, and CHF enhancement of nanofluids are found in data published in the literature. No comprehensive theory explains the energy transfer processes in nanofluids. To bridge the research gaps for nanofluids' engineering application, the urgent work are suggested as follows. (1) Nanofluid stability under both quiescent and flow conditions should be evaluated carefully; (2) A nanofluid database of thermo-physical properties, including detailed characterization of nanoparticle sizes, distribution, and additives or stabilizers (if used), should be established, in a worldwide cooperation of researchers; (3) More experimental and numerical studies on the interaction of suspended nanoparticles and boundary layers should be performed to uncover the mechanism behind convective heat transfer enhancement by nanofluids; (4) Bubble dynamics of boiling nanofluids should be investigated experimentally and numerically, together with surface tension effects, by considering the influences of nanoparticles and additives if used, to identify the exact contributions of solid surface modifications and suspended nanoparticles to CHF enhancement in boiling heat transfer. Once we acquire such details about the above key issues, we will gain more confidence in conducting application studies of nanofluids in different areas with more efficiency.